Spatial distribution of forests and woodlands in Iceland in accordance with the CORINE land cover classification - Björn Traustason 1971-; Arnór Snorrason 1960- (2014)
This paper presents a united geographical database for all known forest and woodland areas in Iceland, both natural and planted. This first edition of the database follows forest and woodland classifications used in the European CORINE land cover program. According to the database, the total area of forests and woodlands in Iceland was estimated as being 156,800 ha, divided into natural downy birch (Betula pubescens) woodland (115,400 ha) and forest plantations (41,400 ha). The natural birch forests were estimated at 23,600 ha and shrubland (<2 m) 91,800 ha. The area of plantation forests was estimated to be 11,300 ha and afforested areas which had not yet reached a height of two meters as 30,100 ha. Accordingly forests and woodlands in Iceland cover 1.5% of the total land surface and 3.6% of the land below 400 m. It was also estimated that 4,000 ha of the forest plantations overlap the natural birch woodlands, amounting to 3.5% of the total natural birch coverage. This is an estimate of the area where natural birch woodlands have been replaced with forest plantations. The database overestimated the area of forest plantations, which indicates that the original mapping of new plantations should be improved. Á Rannsóknastöð Skógræktar ríkisins á Mógilsá hefur verið unnið að gerð landfræðilegs gagnagrunns sem inniheldur upplýsingar um skóglendi landsins, bæði birkilendi og ræktað skóglendi. Flokkun skóga í gagnagrunninum fylgir flokkun skóga í Evrópska CORINE landgreiningarverkefninu. Samkvæmt gagnagrunninum var heildarflatarmál skóglendis á Íslandi áætlað 156.800 ha, þar af var náttúrulegur birkiskógur og kjarr 115.400 ha og ræktað skóglendi 41.400 ha. Náttúrulegir birkiskógar og kjarr skiptust í 23.600 ha af skógi og 91.800 ha af kjarri. Heildarflatarmál ræktaðra skóga var áætlað 11.300 ha en gróðursetningar sem samkvæmt þessu mati höfðu ekki náð 2 m meðalhæð þöktu um þrefalt stærra svæði eða 30.100 ha. Hlutfall skóglendis af yfirborði landsins var 1,5% og 3,6% af landi neðan 400 m hæðar yfir sjávarmáli. ...